Antitrust and (Foreign) Innovation: Evidence from the Xerox Case - Robin Mamrak (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
How does antitrust enforcement against patent-based monopolies affect innovation? I address this question by empirically studying the US antitrust case against Xerox, the monopolist in the market for plain-paper copiers. In 1975, Xerox was ordered to license all its copier-technology patents in the US and abroad. I show that this promoted innovation by other firms in the copier industry, measured by a disproportionate increase in patenting in technologies where Xerox patents became available for licensing. This positive effect is driven by increased innovation by Japanese competitors. They started developing smaller desktop copiers and their innovation became more diverse.
Keywords: O30; O34; L41; K21; 330; antitrust; innovation; patents; compulsory licensing; Japan; Xerox